2015
DOI: 10.3109/03639045.2015.1082582
|View full text |Cite
|
Sign up to set email alerts
|

A novel eye drop of alpha tocopherol to prevent ocular oxidant damage: improve the stability and ocular efficacy

Abstract: The aim of this study was to design novel mixed micelles as an ophthalmic delivery system for alpha-tocopherol (TOC) to prevent its degradation and improve ocular efficacy. The nonionic polymers, Polyoxyl 15 Hydroxystearate (Solutol® HS15) and Pluronic® F127, were discovered to be the most effective agents for retaining the activity and solubilization of TOC, respectively. Prepared by a thin-film hydration method, HS15/Pluronic® F127 yielded good encapsulation percentages of TOC, with a 27.7% drug loading effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In previous studies, our research group has shown that a combination of CsA and vitamin E was a safe and effective treatment for keratoconjunctivitis sicca and chronic superficial keratitis in dogs ( Arteaga et al ., 2021 ). Ophthalmic α -tocopherol (TOC) is the most effective antioxidant of the vitamin E family and is receiving special attention to prevent and treat retinopathies, cataracts, and DES, among other ocular pathologies ( Xin et al , 2016 ). In our study, 100% TOC was used as a new solvent of CsA.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, our research group has shown that a combination of CsA and vitamin E was a safe and effective treatment for keratoconjunctivitis sicca and chronic superficial keratitis in dogs ( Arteaga et al ., 2021 ). Ophthalmic α -tocopherol (TOC) is the most effective antioxidant of the vitamin E family and is receiving special attention to prevent and treat retinopathies, cataracts, and DES, among other ocular pathologies ( Xin et al , 2016 ). In our study, 100% TOC was used as a new solvent of CsA.…”
Section: Discussionmentioning
confidence: 99%
“…For Alzheimer's patients, high cholesterol levels in the blood may hasten the development of beta-amyloid plaques, the clumpy protein deposits that harm to the brain [20]. Therefore, recent studies have been utilized tocopherol (Toc) to enhance liposome stability [21,22]. Since it is not hazardous to the body at any volume, tocopherols give hopefulness for the potential to improve liposome quality [23].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, vitamin E is considered the most important antioxidant present in the body because of its activity against the damaging effects of reactive oxygen species (Mustacich et al 2007;Pekmezci 2011;Peh et al 2016;Miyazawa et al 2019). These properties have fostered the use, in humans, of vitamin E to treat ocular diseases, such as age-related macular degeneration, cataract, uveitis (Xin et al 2016), and to prevent keratocyte apoptosis after refractive surgery (Bilgihan et al 2001). Besides, vitamin E has been shown to protect against UV radiation-induced cataract in albino rat animal models (Ayala and Söderberg 2004).…”
Section: Introductionmentioning
confidence: 99%